2010
DOI: 10.1371/journal.pone.0014030
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Aroma in Transgenic Potato As a Consequence of Impairing Tuber Browning

Abstract: Sensory analysis studies are critical in the development of quality enhanced crops, and may be an important component in the public acceptance of genetically modified foods. It has recently been established that odor preferences are shared between humans and mice, suggesting that odor exploration behavior in mice may be used to predict the effect of odors in humans. We have previously found that mice fed diets supplemented with engineered nonbrowning potatoes (-PPO) consumed more potato than mice fed diets sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Their grazing distribution was recorded for 50 d. There was no significant difference in the grazing preference of the animals [ 110 ]. In another study using a second generation GE potato, both mice and humans actually showed a preference for the aroma of a GE nonbrowning potato as compared to non-GE potatoes [ 111 ]. This effect was not observed when the potatoes were fresh, it was only seen 24 h after the potatoes had aged, presumably associated with the fact that the non-GE potatoes had oxidized and turned brown by that time.…”
Section: Introductionmentioning
confidence: 99%
“…Their grazing distribution was recorded for 50 d. There was no significant difference in the grazing preference of the animals [ 110 ]. In another study using a second generation GE potato, both mice and humans actually showed a preference for the aroma of a GE nonbrowning potato as compared to non-GE potatoes [ 111 ]. This effect was not observed when the potatoes were fresh, it was only seen 24 h after the potatoes had aged, presumably associated with the fact that the non-GE potatoes had oxidized and turned brown by that time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another biotechnological approach successfully applied in potatoes for stacking resistance genes against viruses is RNAi technology ( Missiou et al, 2004 ; Chung et al, 2013 ; Hameed et al, 2017 ). It is important to note that RNAi approach has been successfully employed in a great number of reports for disease and pest resistance ( Waterhouse et al, 1998 ; Missiou et al, 2004 ; Chung et al, 2013 ; Dinh et al, 2015 ; Sun et al, 2016 ; Hameed et al, 2017 ), improved processing quality ( Rommens et al, 2006 ; Llorente et al, 2010 ; Chawla et al, 2012 ; Zhu et al, 2016 ; Hameed et al, 2018 ), and improved nutritional value ( Van Eck et al, 2007 ; Itkin et al, 2013 ; Sawai et al, 2014 ). In fact, the effectiveness of this technology is illustrated in the several commercially approved GE potatoes based on RNAi ( ISAAA, 2021 2 ).…”
Section: Strategies For Potato Transformationmentioning
confidence: 99%
“…Because carotenoid accumulation in plants is the result of multiple processes [ 23 , 76 , 77 ], the combination of various bioengineering strategies, from manipulating the carotenoid biosynthesis and storage mechanisms to installing alternative carotenogenic pathways [ 76 , 78 , 79 , 80 , 81 ] holds potential to take the carotenoid content of crops to a new level. From a holistic point of view, the ultimate synthetic biology approach to make the most of plant-based food on Mars would be to develop multi-biofortified crops with improved nutritional properties [ 82 , 83 , 84 ] and enhanced quality traits (e.g., extended shelf life and reduced allergenicity) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Refactoring Plants For Enhanced Performance On Marsmentioning
confidence: 99%